Bioindication method of soil research in the landfill of municipal solid waste in the North Kazakhstan region in 2016 and 2018 - Lyssakova, T.N.; Nukzhanova, A.M.; Dmitriev, P.S.; Wendt, Jan A. (Fundamental and Experimental Biology, 2019)
The methods of ecological assessment of soil condition in the territory of solid household waste landfills in the North Kazakhstan region are considered in the article. The priority method for studying soil quality in the North Kazakhstan region is the bioindication method. This method shows the state of the soil cover on the landfill site. Based on the results of soil biotesting, different levels of pollution are obtained in the territory of the North Kazakhstan region. This is due to the fact that unauthorized landfills have different years of formation and the garbage stored in landfills has a different composition. In the majority of settlements on land-fills there are remains of animals, organic garbage, liquid wastes. During the experiment, the method of biological monitoring was used in the territory of soliddomestic waste landfills in the North Kazakhstan region. Average soil contamination: Novoishimskoye of the district named after G. Musrepov; Ekaterinovka of Zhambyl district. There is no pollution: Lomonosovka of the district named after G. Musrepov; Chagli of Akkayin district; Svyatodukhovka of Zhambyl district; Rassvet of Kyzylzhar district; Bezlesnoye of Akkayin district; Novokamenka of Kyzylzhar district. Despite the long-term accumulation of solid domestic waste on individual soil samples, seeds of cress-lettuce sprouted even with sprouts with small deviations and slight deformations.